Marketing partnerski jako element innowacyjnego zarządzania regionem - Rabsztyn, Beata (Marketing Based on Partnership as an Element of Innovational Regional Management, 2006)
This document includes information about the essence role and elements of partnership marketing as well as barriers in marketing searches' results which concern identification of new management's elements in local administration units in region of Lodz.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 563-569